2022
DOI: 10.3390/ma15072548
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on Hydrogel–Elastomer Adhesion

Abstract: Hydrophilic hydrogels exhibit good mechanical properties and biocompatibility, whereas hydrophobic elastomers show excellent stability, mechanical firmness, and waterproofing in various environments. Hydrogel–elastomer hybrid material devices show varied application prospects in the field of bioelectronics. In this paper, the research progress in hydrogel–elastomer adhesion in recent years, including the hydrogel–elastomer adhesion mechanism, adhesion method, and applications in the bioelectronics field, is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 109 publications
0
5
0
Order By: Relevance
“…Indeed, the AM 20 -Ca 2+ hydrogel can adhere to various surfaces including human skin, plastic, glass, wood, metal, rubber, and paper (Figure A). , The adhesion mechanism of hydrogels with the human skin is attributed to the hydrogen bonding and electrostatic interaction of a protein molecule in tissue with the carboxyl groups of the hydrogel. These hydrogels adhere to the polypropylene plastic substrate and nitrile rubber substrate through hydrophobic interactions. Besides, strong adhesion of hydrogels with glass, wood, and paper occurs through the H-bonding interactions. The adhesive strength of AM 20 -Ca 2+ was quantitatively assessed through a lap shear test on metal, glass, rubber, and plastic substrates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the AM 20 -Ca 2+ hydrogel can adhere to various surfaces including human skin, plastic, glass, wood, metal, rubber, and paper (Figure A). , The adhesion mechanism of hydrogels with the human skin is attributed to the hydrogen bonding and electrostatic interaction of a protein molecule in tissue with the carboxyl groups of the hydrogel. These hydrogels adhere to the polypropylene plastic substrate and nitrile rubber substrate through hydrophobic interactions. Besides, strong adhesion of hydrogels with glass, wood, and paper occurs through the H-bonding interactions. The adhesive strength of AM 20 -Ca 2+ was quantitatively assessed through a lap shear test on metal, glass, rubber, and plastic substrates.…”
Section: Resultsmentioning
confidence: 99%
“…These hydrogels adhere to the polypropylene plastic substrate and nitrile rubber substrate through hydrophobic interactions. 41 43 Besides, strong adhesion of hydrogels with glass, wood, and paper occurs through the H-bonding interactions. The adhesive strength of AM 20 -Ca 2+ was quantitatively assessed through a lap shear test on metal, glass, rubber, and plastic substrates.…”
Section: Resultsmentioning
confidence: 99%
“…35 With significantly growing demands of functional ductile elastomers in advanced technologies, their adhesive properties play a critical role in determining their lifetime and reliability in the designated fields. [36][37][38][39][40][41][42][43][44][45] The incorporation of intermolecular interactions is an important strategy to improve the adhesive properties of elastomers. For example, Chen et al and Tan et al independently demonstrated that the incorporation of a small number of hydrogen-bonding 2-ureido-4[1H]pyrimidinone (UPy) groups enhanced the adhesion force of the elastic materials to organic and inorganic substrates for finger strain sensors and soft robot actuators.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8]. The advantages of surface modification of elastomers include the preservation of useful volumetric properties of rubber along with improvement of the surface characteristics (antifriction properties, resistance to aggressive media, and ultraviolet radiation) [9][10][11]. Coatings on the rubber surface are produced in various ways: Plasmochemical treatment of elastomer surface [12,13], ion-plasma application of a metal layer [14], application of durable and wear-resistant polymers [15,16], and production of hybrid materials [17,18].…”
Section: Introductionmentioning
confidence: 99%